Pengambilan Kebijakan Berbasis Education Management Information System(EMIS) - Aziz, Fuadi (Jurnal Pendidikan Islam, 2014)
Education Management Information System (EMIS) is intended to provide real data to support the decision maker. The study aims to describe and analyze the implementation of EMIS in making decision in ‘Mapenda’ of the Ministry of Religious of ‘Gunungkidul’ district. The results showed that EMIS that is as the basis of educational data base for making policy has not been able to use it well. Data of EMIS is only used as an initial data and it is done to cross-check through direct meetings or through telephone communication that requires a lot of time.The obstruction is the process of EMIS data collection that is done only at a certain time, so the data is not updated, the issues of EMIS application, the ability to manage EMIS, and the participation of headmaster with the data collection.